Gerakan Asas Senaman Tua (ST) Melayu bagi Meningkatkan Kesihatan Am - Ros Aiza Mohd Mokhtar; Adibah Sulaiman; Sharifah Najwa Syed Mohamad; Fathima Begum Syed Mohideen; Latifah Mustafa (Universiti Sains Islam Malaysia, 2025)
Sains Insani, Volume 9 Issue 2 Page (161-170)